Deadly Weapons Concealed, Etc., & Shooting Firearms, Ch. 30, § 184, in Revised Ordinances City of Sarcoxie, Jasper County, MO (1907). - (:unkn) unknown (General Publisher, 1907)
Deadly Weapons Concealed, Etc. If any person shall carry concealed upon or about his person any deadly or dangerous weapon, or shall go into any church or place where people have assembled for religious worship, or into any school room or place where people are assembled for educational, literary or social purposes or to any election precinct on any election day, or into any court room during the sitting of court, or into any other public assemblage of persons met for any lawful purpose other than for militia drill, or meeting called under the militia law of this State, having upon or about his person any kind of fire arms, bowie knife, dirk, dagger, slung shot or other deadly weapons, or shall in the presence of one or more persons exhibit any such weapon in a rude, angry or threatening manner, or shall have or carry any such weapon upon or about his person when intoxicated, or under the influence of intoxicating drinks, or shall directly or indirectly sell or deliver, loan or barter to any minor any  such weapon without the consent of the parent or guardian of such minor, he shall be deemed guilty of a misdemeanor and upon conviction be punished by a fine of not less than fifty [$50.00] dollars nor more than two hundred [$200.00] dolars, or by imprisonment in the city jail not less than five days nor more than six months
--
Keywords: CARRY - CONCEALED; TRANSFER - MINORS; BRANDISHING; SENSITIVE PLACES